Synergistic anion–π interactions in peptidomimetic polyethers - Seunghyun Lee; Aram Shin; Jinwoo Park; Sowon Yun; Minseong Kim; Dong Woog Lee; Byeong-Su Kim (Proceedings of the National Academy of Sciences, 2025)
Anion–π interactions are crucial in various biological processes, such as enzyme catalysis and ion transport. Despite their significance, the exploitation of anion–π interactions in synthetic polymer systems remains underexplored. This study investigates anion–π interactions using chemically well-defined peptidomimetics guided by the composition of mussel foot proteins. Specifically, polyether-based polymers were designed utilizing two functional epoxide monomers—catechol acetonide glycidyl ether and 4,4-dimethyl-2-oxazoline glycidyl ether—to mimic the key amino acids 3,4-dihydroxyphenylalanine and aspartic acid, respectively. A surface forces apparatus was employed to study the anion–π interaction between the polymers, considering the effects of relative monomer composition and pH conditions. The maximum cohesion energy of 15.0 mJ/m 2 was observed at an equimolar monomer composition at pH 7. Incorporating a phenyl group instead of the catechol group and introducing competing anions confirmed the dominant role of anion–π interactions. This study highlights the significance of anion–π interactions, posing a high potential in the design and synthesis of functional materials.